Research Trend of Accounting Employability through Bibliometric Analysis - Saputri, Fadhilah Mahanani; Siswandari, S; Setyowibowo, Feri (Proceedings International Conference on Education Innovation and Social Science, 2023)
The purpose of this research is to analyze the scientific trend of accounting employability through bibliometric studies in the Scopus database from 1981 to mid-2023. During the study period, 1,815 documents were found in the Scopus database. Geographically, United Kingdom is a productive country with 335 articles. The results of the bibliometric analysis show that the writers of accounting employability who are productive and often collaborate are Baruch, Asonitou, Alnoor. The institutions that most frequently publish accounting employability are Edith Cowen University, Universiti Sains Malaysia, and KU Leuven. Bibliometric analysis also found that there were 134 items that were correlated with accounting employability which were divided into 7 clusters. Keywords that often appear in student accounting employability relate to knowledge, skills, personal attributes, values and ethics, career development, career adaptation, technology, work integrated learning and internships, learning approaches, curriculum, accounting education, entrepreneurship education, assessment, company organization and education, barriers, and challenges. Research from 1981 to 2023 is growing where the education domain is increasingly connected with various crisis conditions, economic conditions, education management which results in the possibility of future research based on the gaps found and the development of accounting employability in various research methods.